PELATIHAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN NUMERASI PESERTA DIDIK BAGI GURU SEKOLAH DASAR - Fauzi, Asri; Indraswati, Dyah; Sobri, Muhammad; Rahmatih, Aisa Nikmah; Amrullah, Lalu Wira Zain (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
One effort that can be made to improve students' numeracy skills is by implementing differentiated learning strategies. Differentiated learning is a method used by teachers to meet the needs of each student so that students can learn material according to their abilities, talents and interests as well as their individual needs so that they do not feel like they have failed in their learning experience. In differentiated learning, 3 aspects can be distinguished so that students can understand the learning material: the content, the process, and the product. Based on this, the service team conducted differentiated learning training to improve students' numeracy skills for teachers at SDN 23 Mataram. This training aims to increase teacher knowledge in implementing differentiated learning. Based on the results of community service activities that have been carried out, it can be said that these activities ran smoothly according to the planned schedule and were successful. The participants were enthusiastic about the training because, in the independent curriculum, all teachers must understand differentiated learning. The level of understanding of participants in implementing differentiated learning after training. Based on this, the level of knowledge of participants in the very understanding category was 55% or 6 out of 11 participants. Then the understanding category was 36% or 5 participants, and the quite understanding category was 9% or only 1 participant.